Entomological Investigation and Detection of Dengue Virus Type 1 in Aedes (Stegomyia) albopictus (Skuse) During the 2018–2020 Outbreak in Zhejiang Province, China - Liu, Qinmei; Wang, Jinna; Hou, Juan; Wu, Yuyan; Zhang, Hengduan; Xing, Dan; Gao, Jian; Li, Chunxiao; Guo, Xiaoxia; Jiang, Yuting; Gong, Zhenyu; Zhao, Tongyan (Frontiers in Cellular and Infection Microbiology, 2022)
Mosquito-borne diseases are still threats to public health in the Zhejiang province of China. Surveillance of mosquitoes and the mosquito-borne pathogen is a vital approach for early warning, prevention, and control of the infectious disease. In this study, from 2018 to 2020, a total of 141607 female mosquitoes were caught by means of the light trap method. The main species were Culex pipiens quinquefasciatus/pallens (41.32%), Culex tritaeniorhynchus (47.6%), Aedes albopictus (2.5%), Anopheles sinensis (5.87%), Armigeres subalbatus (2.64%) and other mosquito species (0.07%). Cx. pipiens s.l. were the dominant species in two urban habitats and rural residential areas while Cx. tritaeniorhynchus was the main dominant species in the rural livestock sheds. In terms of seasonal fluctuation, Cx. pipiens s.l fluctuated at a high level from May to October. The peaks of Cx. tritaeniorhynchus, An. sinensis and Ar. subalbatus were in July. In addition, a total of 693 Ae. albopictus were collected with Biogents Mosquitaire CO2 traps in emergency surveillance of dengue fever (DF) and screened for dengue virus infection. There were three circumstances of collection: The first: the sampling time before mosquito control during the local outbreak of DF in Lucheng of Wenzhou, 2019; The second circumstance: the sampling time after mosquito control during the local outbreak of DF of other cities in 2018-2019; The third circumstance: past DF epidemic areas the sampling time before mosquito control during the local outbreak of DF in Lucheng, Wenzhou, Zhejiang, 2019. The pools formed by mosquitoes collected in these three circumstances were 3 (6.1%), 35 (71.5%), and 11 (22.4%) respectively. Of the 49 pools tested, only one in the first circumstance was positive. The full-length dengue virus sequence of ZJWZ/2019 was obtained by sequencing and uploaded to the NCBI as number OK448162. Full-length nucleotide and amino acid homology analyses showed that ZJWZ2019 and Wenzhou DF serum isolates ZJWZ-62/2019 (MW582816) and ZJWZ-18/2019 (MW582815) had the highest homology. The analysis of full genome and E gene phylogenetic trees showed that ZJWZ2019 belonged to serotype 1, genotype I, lineage II, which was evolutionarily related to OK159963/Cambodia/2019. It implies that ZJWZ2019 originated in Cambodia. This study showed the species composition, seasonal dynamics of mosquitoes in different habitats in Zhejiang province and confirmed the role of Ae. albopictus in the transmission cycle of in outbreak of DF in the Lucheng district of Wenzhou in 2019, suggesting the importance of monitoring of vector Aedes infected dengue virus in the prevention and control of DF.